(untitled) (Global Journal of Medical Research, 2023)
Background: Hypovitaminosis D is commonly prevalent in older population world over leading to increased levels of bone resorption, reduced bone mass, often resulting inosteoporosis and increased chances of falls and fractures. In children, vitamin D deficiency is known to cause rickets due to hypomineralization of bone.